Appearing competent or moral? The role of organizational goals in the evaluation of candidates - Fousiani, Kyriaki; Van Prooijen, Jan-Willem; Armenta, Bibiana (Frontiers in Psychology, 2022)
The Big Two theoretical framework suggests that two traits, namely morality and competence, govern social judgments of individuals and that morality shows a primacy effect over competence because it has more diagnostic value. In this study we tested the primacy effect of morality in the workplace by examining how instrumental or relational goals of organizations might influence the importance of morality or competence of candidates during the hiring process. We hypothesized that the primacy effect of morality might hold when organizational goals are relational, but it might get reversed when organizational goals are instrumental. Supporting our hypothesis, in a field study and two experiments (both preregistered) we found that people perceive moral candidates as more appropriate for recruitment when an organization prioritizes relational goals (Studies 1, 2, and 3). In contrast, people perceive competent candidates as more appropriate for recruitment when an organization prioritizes instrumental goals (Studies 1 and 2). Perceived appropriateness of a candidate, in turn, predicts a stronger intention to recruit a candidate (Studies 2 and 3). These results provide evidence for a reversal of the primacy effect of morality in a work setting, and illuminate the important role of organizational goals in social judgments.